HUBUNGAN LAMA PENGGUNAAN ALAT ORTODONTIK CEKAT TERHADAP AKUMULASI PLAK DAN pH SALIVA MAHASISWA FKG-UMI TAHUN 2017 - Lestari, Nurasisa; Puspitasari, Yustisia; Masdar, Tri Audia (Jurnal Ilmiah As-Syifaa, 2018)
Orthodontic treatment is a form of treatment in the field of dentistry which plays an important role in improving dental structure. Fixed orthodontic tools have an important role to obtain optimal and harmonic occlusion. Orthodontic appliance also affects plaque accumulation and salivary pH so that it can cause various dental and oral diseases The purpose of this study was to determine the relationship between the length of fixed orthodontic use to plaque accumulation and salivary pH of FKG UMI students in 2017. This study was an analytic observational, cross sectional study method.The sample of this study was FKG UMI students who used fixed orthodontics, sampling techniques with total sampling.Statistical test used Independent Samples Test. The results of this study showed <12 months long fixed orthodontic use of 30.8% and> 12 months of 69.2%. Based on plaque accumulation the highest score was 74.4%. Based on salivary pH the highest score is acid 94.9%, and based on statistical tests obtained a significant value of p = 0.001 (<Î± = 0.05). The results showed that there was a correlation between the length of fixed orthodontic use of plaque accumulation and salivary pH of FKG-UMI students in 2017.